Assessing Uptake of COVID-19 Preventive Measures among Persons Aged 13-80 Years during Lockdown in Wakiso, Uganda: A Cross-Sectional Study - Alex Daama; Fred Nalugoda; Robert Bulamba Malyabe; Nkale Menya James; Stephen Mugamba; Emmauel Kyasanku; Juliana Namutundu; Edward Nelson Kankaka; Gertrude Nakigozi; Godfrey Kigozi (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: The unprecedented spread of COVID-19 presents a serious public health concern. However, uptake of COVID-19-related preventive behaviors remains unknown. This study aimed to investigate current uptake of COVID-19 preventive measures and their associated factors in Wakiso, Uganda.Subjects and Method: A cross-sectional study was conducted in Wakiso, Uganda from April to September 2020. A total of 1,014 study subjects aged 13–80 years in the population health survey (PHS) who self-reported following any of the COVID-19 preventive behavioral strategies during lockdown was selected. The dependent variable was COVID-19 preventive measures. Independent variables were gender, age, education, marital status, religion, occupation. The data were collected by questionnaire and analyzed using Modified Poisson regression test.Results: Female (aPR=1.48; 95% CI= 1.34 to 1.62; p<0.001), construction and mechanics workers (aPR=1.23; 95% CI= 1.10 to 1.38; p<0.001), housework (aPR= 0.72; 95% CI= 0.64 to 0.81; p <0.001), and students (aPR=0.58; 95% CI= 0.45 to 0.74; p<0.001) were associated with staying at home. Aged 45-54 years old (aPR=0.55; 95% CI= 0.50 to 0.61; p<0.001), more than 55 years (aPR=0.80, 95% CI= 0.66 to 0.97; p= 0.022), and housework (aPR=1.18; 95% CI= 1.03 to 1.35; p= 0.015) were associated with sanitize often.Conclusion: Female, construction and mechanic workers, housework, and student are associated with staying at home and it is statistically significant. Aged 45-54 and more than 55 years old, housework were associated with sanitize often and it is statistically significant.Keywords: preventive measures, COVID-19, Wakiso, UgandaCorrespondence:Alex Daama. Africa Medical and Behavioral Sciences Organization (AMBSO). Plot 7441, Nansana, Hoima Road, Wakiso, Uganda P.O Box 25974. Email: daamaalex6141@gmail.com. Mobile: +256702347102Journal of Health Promotion and Behavior (2021), 06(02): 153-162DOI: https://doi.org/10.26911/thejhpb.2021.06.02.08